Drinking water principles and practices - Moel, P.J. de (Peter J. de) 1954- (World Sciencetific Publishing, 2006)
Provides a comprehensive overview of all the major aspects of modern drinking water systems in the western European context. This book covers the theoretical principles, and also the historical background and practical aspects of design and operation, legislation, planning and finance of drinking water supply in its social and economic context.